Problems and Prospects for the Development of Professional Pedagogical Activity in the Context of IT Penetration into Educa-tion - Mikhailenko, Olga Ivanovna (2020)
The beginning of the 21st century was marked by the rapid growth of qualitative transformations in all spheres of public life, including in pedagogical activity. Undoubtedly, this was facilitated by the steady development of information and communication technologies (ICT), the transformation of knowledge into a fundamental source of welfare gain as for a separate individual, and for society as a whole. Today, cross-cultural competencies are actively being formed that create opportunities for self-identification of individuals and communities; the dominance of the role of information-filled factors in the composition of sources of information-analytical base, etc. are observed. All this allows us to talk about the formation of the information society, which determines the transformation of professional pedagogical activity and its institutional environment. In our opinion, there is a change in the content of pedagogical activity; it is being transformed into information and analytical activity, as it is implemented by carriers of intellectual and creative resources with the active use of breakthrough information and communication technologies, which, ultimately, allows us to provide the main contribution to improving the level of professional development teacher. It is about the formation of a global information space. Experts note that teachers of non-pedagogical specialties of higher educational institutions in the Russian Federation often do not have basic pedagogical education, which makes it very difficult and even impedes the solution of many educational problems, not to mention the fact that they do not have a proactive character regarding the state of educational practice. Speaking about the teachers’ availability of professional and pedagogical training, we assume that, at a minimum, they know such methods of professional pedagogical activity as the algorithmization and problematization of the educational dialogue, which allow them to identify the operations of the activity and determine their optimal sequence; all this also actively involves students in discussions when considering problem situations, etc. All that, in the end, is associated with the need to find relevant information for a professional solution to the problem in question. It is obvious that in modern realities it is necessary to constantly update professional information due to its rapid obsolescence, which in itself requires the active improvement of pedagogical technologies. All this speaks of the need to improve the theoretical and methodological provisions and practical recommendations of professional and pedagogical training of university teachers in the conditions of informatization of education.